Cardiac Arrest and Successful Extracorporeal Cardiopulmonary Resuscitation as a Result of a Refeeding Syndrome in a Young Female with Anorexia Nervosa. (28th July 2020) - Waddell, Daniela; Meincke, Felix; Hakmi, Samer; van der Schalk, Hendrick; Schenker, Niklas; Hahn, Jonas; Moschner, Anna; Bohné, Mintje; Chung, Da-Un; Willems, Stephan; Kivelitz, Dietmar; Bahlmann, Edda
Abstract : Anorexia nervosa is a potentially life-threatening eating disorder, characterized by an abnormally low body weight. This case report illustrates a 22-year old female with cardiac arrest due to a refeeding syndrome in a patient with anorexia nervosa. It features the successful use of extracorporeal cardiopulmonary resuscitation in a case of severe left ventricular dysfunction resulting in a favorable outcome. Conclusion . We present the first case of a cardiac arrest due to a refeeding syndrome in anorexia nervosa featuring the successful use of an extracorporeal cardiopulmonary resuscitation approach as a bridge to full recovery.